Science Library Trends at ARL Institutions - Chris Doty; Kristan Majors (Issues in Science and Technology Librarianship)
This study uses qualitative and quantitative data to identify science library trends at Association of Research Libraries (ARL) member institutions. Our recent count found 69% of all ARL academic institutions have at least one science library. Comparing our data to a 2010 study of American ARL institutions, the number of science libraries at American ARL institutions is down 17%. Our analysis shows this decrease is due in large part to a continuing trend of departmental libraries (e.g., mathematics, chemistry, and physics) merging into multidisciplinary science libraries. We also surveyed ARL science libraries and found that their primary focus is on providing comfortable, inviting study space and promoting student and/or faculty collaboration. Both datasets from this study can be used to support the ongoing management of science libraries, including collections, facilities, and services.